Pengaruh Gaya Berpikir Siswa Terhadap Hasil Belajar IPS Siswa Kelas VIII SMP Negeri 3 Kota Solok - Basyirun, Fajri; Oktavia, Nina (Jurusan PIPS FKIP UMMY Solok, 2017)
This study is based on the low learning outcomes of students allegedly influenced by divergent thinking styles such as the level of mastery is still low. The goal to be achieved in this study is to find out how much influence the student's thinking style on the learning outcomes IPS students of class VIII SMP Negeri 3 Solok city. This type of research is quantitative. The population were students of SMP Negeri 3 Kota Solok, there are 68 students. This study uses total sampling technique. The technique used in this research is simple linear regression analysis technique. The results of this study indicates that: the style of thinking has ???????????????????????? equal to 3.685 while ???????????????????????? equal to 1,995. So the conclusion in this study is there is a positive and significant influence between the thinking style on the student's learning outcomes. Based on data analysis whereas statistic by using t test, it is known that thinking style have ???????????????????????????????????????????????? 3.685 while ???????????????????????? equal to 1,995, this means ???????????????????????????????????????????????? > ???????????????????? then ???????? rejected ???????? accepted. So the conclusion that there is a significant influence between students' thinking styles on the learning outcomes IPS class VIII students in SMP Negeri 3 Kota Solok. For the researcher to increase the researcher's perspective on student's thinking style about IPS teacher in realizing good learning condition, for students is to improve their learning achievement optimally, for teachers can be as reference and guidance in preparing lesson that can improve learning objectives.